2018
DOI: 10.1021/acs.jafc.8b03590
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Wheat Glutaredoxin and Its Application in Improving the Processing Quality of Flour

Abstract: Glutaredoxin (Grx) is a ubiquitous oxidoreductase that plays a vital role in maintaining cellular redox homeostasis. In comparison to Grx from other organisms, plant Grx is unique in that it has many isoforms, which, thus, suggests probably diverse functions and mechanisms. Therefore, structure−function characterization of plant Grx is necessary to have indepth knowledge and explore its application in industry. In this study, wheat Grx (wGrx) was overexpressed and purified and the crystal structure of wGrx was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The storage modulus is a measure of the ability of an object to resist elastic deformation, and the loss modulus reflects the viscosity of the material. 45 Figure 6 shows that G′ was significantly (p < 0.05) higher than G″ in all the doughs, indicating that elasticity is dominant, and all the doughs possessed solidlike properties. Compared to DY, the changes in G′ and G″ of DOA, DLB-1, and DYLB-1 were more obvious.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The storage modulus is a measure of the ability of an object to resist elastic deformation, and the loss modulus reflects the viscosity of the material. 45 Figure 6 shows that G′ was significantly (p < 0.05) higher than G″ in all the doughs, indicating that elasticity is dominant, and all the doughs possessed solidlike properties. Compared to DY, the changes in G′ and G″ of DOA, DLB-1, and DYLB-1 were more obvious.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…The dynamic rheological parameters, including the storage modulus ( G ′) and loss modulus ( G ″), of different doughs during the fermentation stage are depicted in Figure . The storage modulus is a measure of the ability of an object to resist elastic deformation, and the loss modulus reflects the viscosity of the material Figure shows that G ′ was significantly ( p < 0.05) higher than G ″ in all the doughs, indicating that elasticity is dominant, and all the doughs possessed solidlike properties.…”
Section: Resultsmentioning
confidence: 99%
“…8,11 It was reported that wheat glutaredoxin together with wheat thioredoxin has a positive effect on flour and dough properties and bread making. 12 Catalase (EC 1.11.1.6), which catalyzes the decomposition of hydrogen peroxide, mostly exists in aerobic living organisms to protect the cells from oxidative stress triggered by overproduced hydrogen peroxide. 13 Furthermore, catalase also catalyzes the peroxidation of phenols, formic acid, formaldehyde, and alcohols.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Actually, in recent years increasing evidence has shown that redox enzymes could affect the processing quality of flour and dough. Previous research showed that wheat endoplasmic-reticulum oxidoreductin 1 (wEro1), glucose oxidase, and pyranose oxidase could enhance mixing characteristics and viscoelastic properties of dough. , It was reported that wheat glutaredoxin together with wheat thioredoxin has a positive effect on flour and dough properties and bread making …”
Section: Introductionmentioning
confidence: 99%